Thursday

April 17, 2014

April 17, 2014

Posted by **alejandra** on Wednesday, September 13, 2006 at 12:20am.

correct

You can drop the parentheses and rearrange the terms to get

(4q+2)-(2q-3)=4q-2q + 2-(-3)=2q+5

definately correct! i don't think that it is that hard if you drop the brackets you can't doubt it!

**Related Questions**

Math help please!!! - Factor completely 3p^2q + 9p^2q^2 - 12p^2q^3 I have done ...

Differential Calculus - Given that p=(2q^2-5)^2. when q=3, it is increased by 0....

Math - how do i solve 2q/(2q+3)-2q/(2q-3)=1

Math - What do you get when you factor 2q^2+22q=-60? Is there more than one ...

Physics electric force, please help! - A charge of +Q and a charge of +2Q are ...

physics - A charge of +Q and a charge of +2Q are separated by a distance r. The ...

Physics..an electric field - 4 charged particles are at the cornedrs of a square...

Math - Simplify each expression. Write answers in standard form. a. (4d-6)(-3d) ...

math algebra - 9p +2q-4(6p-2q) simplified

Math - 5p+2q=3 7p+2q=11